Urban Agriculture : Findings from Four City Case Studies - World Bank (Washington, DC, 2013)
Urban agriculture contributes to local economic development, poverty alleviation, the social inclusion of the urban poor and women, as well as to the greening of the city and the productive reuse of urban wastes. Urban agriculture encompasses a wide variety of production systems in both urban as well as peri-urban areas. This study examines the contribution of urban agriculture to livelihoods, food security, health, and the urban environment through an assessment of existing urban agriculture activities among poor households in four selected cities. Another important benefit from urban agricultural production is in the cash savings from self-produced food that would otherwise have to be purchased. The role and importance of urban agriculture will likely increase with urbanization and climate change, so the integration of urban agriculture into development strategies and policy decisions would be important for long-term sustainability. This report is structured according to the basic framework mentioned above. Chapter two then summarizes the key findings from the four city case studies, analyzing the profiles of urban agriculture in each city, including the agricultural practices pursued, access to and use of urban land, as well as examining the available data for evidence of the importance of urban agriculture for livelihoods and food security. Chapter two also discusses the main findings from the case studies on the constraints facing urban agriculture. Chapter three then provides various recommendations for strengthening urban agriculture and addressing these constraints, recognizing that these need to be considered in light of the broader urban development agenda and the many competing priorities that cities face. The annexes to this report describe the methodology used for the city case studies, and provide detailed information on each city, including a general city profile, the urban agricultural practices in each city, the inputs used and outputs produced, and the income, expenditure, dwelling and food consumption profiles of residents.